Electronic Excited State of Alizarin Dye Adsorbed on TiO2 Nanoparticles: A Study by Electroabsorption (Stark Effect) Spectroscopy - Nawrocka, Agnieszka; Krawczyk, Stanisław (Journal of physical chemistry. C, 2008)
Alizarin is one of the dyes extensively investigated as an example of a molecule capable of serving as a light absorber and an electron donor in model systems designed for the new type solar cells. Using the Stark effect measurements for alizarin, both free in solution and adsorbed to TiO2 nanoparticles, the question has been addressed whether the excited-state orbital of adsorbed alizarin extends into the solid and involves the orbitals of the Ti atom or remains localized within the alizarin molecule. Because an important role can be played by the electric field at the charged surface of the nanoparticles, the field was modulated by changing the pH of the medium. The results reveal a substantial dipole moment change on the electronic excitation of the alizarin−TiO2 system, |Δμ| ≈ 10 Debye units or slightly more. The observed dependence of the absorption maximum and the measured |Δμ| on pH were used to distinguish between Δμ directed toward the nanoparticle surface and that corresponding to the intrinsic rearrangement of electrons within alizarin or, in reverse direction, corresponding to more- or less-complete electron transfer from alizarin onto the orbitals of Ti and adjacent atoms comprising a localized surface (or a delocalized conductive) state. The results qualitatively contradict a significant dye-to-solid charge-transfer character of the electronic transition. It is shown that they can be interpreted in a self-consistent way by considering, in a first approximation, the light absorption by alizarin monoanion subject to the electric field generated by the charged nanoparticle surface.